Impact of Cognitive Behavior Coping Skills on Relapse Prevention in Individuals with Methamphetamine Use Disorder - Iftikhar Ahmad; Dr Farhana Kazmi; Dr. Sher Dil (Research Journal of Psychology, 2025)
Methamphetamine use has spread throughout the world, needing a thorough assessment of the efficacy of different therapeutic approaches. The effectiveness of cognitive behavior coping skills in preventing relapses in methamphetamine addicts was assessed in this study. People with methamphetamine dependence at addiction treatment and rehabilitation facilities in Pakistan participated in a randomized controlled trial. The study hypotheses were evaluated using four questionnaires. A total of 60 participants were split into two groups: 30 in the experimental group and 30 in the control group. Relapse rates were significantly lower in the treatment group. In order to help people manage methamphetamine cravings as a chronic stressor that threatens recovery from substance use disorder, these findings highlight the significance of cognitive-behavioral coping skills in promoting positive emotions. which could be crucial in assisting people in controlling methamphetamine cravings, a persistent stressor that jeopardizes substance use disorder recovery. Significant changes were found to originate within subjects, according to the results of the Repeated Measure ANOVA, which was conducted using SPSS 26. The results indicate significant group differences on the variables of aggression, methamphetamine craving, coping skills, and stimulant relapse risk. The results of this study demonstrated that cognitive behavior coping skills interventions can lower aggression and craving levels as well as the likelihood of relapse in people with methamphetamine use disorder. Cognitive behavior interventions are also recommended as a treatment for improving personnel factors like self-efficacy and quality of life coping. According to the study’s findings, providing cognitive behavior coping skills to an experimental group in an inpatient setting was both feasible and successful when compared to standard inpatient treatment. Cognitive behavior coping skills (CBCS) were found to be effective in preventing relapses in methamphetamine-dependent individuals. This study will further our understanding of CBCS as an evidence-based intervention for substance use disorders.